PENENTUAN WAKTU BAKU UNTUK PROSES PENGELOLAAN LIMBAH B3 DI PT XYZ - Nanta Sigit; Ananda Dwi Novitasari; Wildan Liulil Abshor; Zacky Ardana Putra Ismail (CV. Denasya Smart Publisher, 2026)
PT XYZ is a manufacturing company in the automotive sector that produces vehicles and their components. Its production process generates hazardous and toxic (B3) waste classified as fast moving due to its high volume and frequency. This study aims to determine the standard time for the management process of iron gram B3 waste at PT XYZ. Observations were conducted over 15 cycles, with time recorded at each stage using the stopwatch time study method and adjustments based on the Westinghouse technique. The study was carried out across eight stages of the B3 waste management process at PT XYZ, involving calculations of cycle time, normal time, and standard time. The analysis revealed that the total standard time for the entire process is 42 minutes and 18 seconds. Establishing this standard time supports improved efficiency, prevents waste accumulation, and creates a more structured waste management system that can be periodically evaluated.